Reproducing Patriarchy in Digital Islam: A Feminist Critical Discourse Analysis of Women’s Leadership Narratives on Muslimahnews.net - Abidin, Achmad Azis; Musyafiq, Ahmad; Purwaningsih, Sri; Rochmawati, Nikmah (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
This article examines the reproduction of patriarchal interpretations of women’s leadership within contemporary digital Islamic discourse, focusing on Muslimahnews.net. Employing a feminist Critical Discourses Analysis framework developed by Sara Mills and integrating insights from digital religion theory, particularly those of Heidi Campbell and Gary Bunt, the study analyzes how hadith narratives are discursively mobilized to construct and legitimize gender hierarchy. Through content analysis of a leadership-related article, the findings reveal that patriarchal authority is naturalized through selective intertextuality, subject-object positioning, and affective moral framing, which present male leadership as normative and divinely sanctioned while delegitimizing women’s public roles. The platform operates as a digital node within a broader cyber-Islamic environment, where networked participation, shifting religious authority, and algorithmic circulation reinforce ideological coherence. This study argues that patriarchal ideology in digital Islam is sustained through the interplay of discourse, technological mediation, and affective engagement, offering a critical contribution to scholarship on gender, religion, and digital media.